Development of Interactive Learning Multimedia on Harmony Materials in the Ecosystem - Donna Rhamdan; Neni Novitasari; Tazkiyah Mufidah (Justek : Jurnal Sains dan Teknologi, 2026)
This research aims to develop interactive learning multimedia that is feasible and interesting. This research uses research and development (R&D) methods with research and development procedures using the ADDIE Model which consists of several stages, namely: Analyze, Design, Develop, Implement, and Evaluate. Then the sampling technique used was the saturated sampling technique, where the sample taken used all members of the population, namely 27 students. The model focuses on a systematic learning process. The products that have been designed, validated by subject matter experts with an average percentage of 95% with a very feasible category, validation by linguists with an average percentage of 85% with a very feasible category, validation by design experts with an average percentage of 95% with a very feasible category, and assessments from practitioners in the form of teacher response questionnaires to interactive learning multimedia developed by researchers get a percentage of 95% with the category very feasible, and the average percentage of student response questionnaires for the trial use is 95% with a very interesting category. Based on the description above, it can be concluded that feasibility is determined by the validation results from experts and practitioners as well as the attractiveness of student responses. Furthermore, this research on the development of interactive learning multimedia still focuses on the subject of harmony in ecosystems. Therefore, further research is expected to expand to other abstract and difficult-to-understand materials for students.